Incidence and risk factors of Pneumocystis jirovecii pneumonia in Korean patients with inflammatory bowel disease. Issue 2 (1st September 2019) - Nam, Kwangwoo; Park, Sang Hyoung; Lee, Junghwan; Jo, Seokjung; Kim, Seon‐Ok; Noh, Soomin; Park, Jae Cheol; Kim, Jin Yong; Kim, Jeongseok; Ham, Nam Seok; Oh, Eun Hye; Song, Eun Mi; et al.
Abstract: Background and Aim: Little is known whether routine prophylaxis against Pneumocystis jirovecii pneumonia (PJP) is needed in patients with inflammatory bowel disease (IBD) on immunosuppression, especially in Asian populations. We, therefore, sought to investigate the incidence and risk factors of PJP in patients with IBD in Korea. Methods: We investigated the incidence of PJP in patients with IBD and compared the characteristics of IBD patients with PJP episodes (IBD‐PJP group) with those of matched controls (IBD‐only group) using a large, well‐characterized referral center‐based cohort. Results: Among the 6803 IBD patients (3171 with Crohn's disease and 3632 with ulcerative colitis) enrolled in the Asan IBD Registry between June 1989 and December 2016, six patients (0.09%) were diagnosed with PJP. During the 57 776.0 patient‐years of follow‐up (median 7.2 years per patient), the incidence of PJP was 10.4 cases per 100 000 person‐years, and none of these patients had received PJP prophylaxis. In case–control analysis, the IBD‐PJP group ( n = 6) showed significantly higher C‐reactive protein level at diagnosis of IBD ( P = 0.006), as well as higher exposure to corticosteroids ( P = 0.017), than did controls ( n = 24). In addition, the IBD‐PJP group showed higher rates of double (50% vs 12.5%) or triple (33.3% vs 4.2%) immunosuppression than did controls, although these are not statistically significant. Conclusions: Although the incidence of PJP in Korean patients with IBD is low, careful monitoring is necessary for the early detection of PJP. In addition to the patients receiving double or triple immunosuppression, PJP prophylaxis should be considered especially in patients with severe disease activities requiring corticosteroids.